+0  
 
0
848
1
avatar+346 

4x(2x^2 − 7x + 3)

 Jun 17, 2014

Best Answer 

 #1
avatar+121078 
+5

Let's take it term by term

4x* 2x^2  =  4*2*x*x^2  =  8x^3

4x *(-7x) =  4*(-7)*x*x = -28x^2

4x*3 = 4*3*x = 12x

Put it all together...

8x^3 - 28X^2 + 12x

And that's it ... !!!

 

 Jun 17, 2014
 #1
avatar+121078 
+5
Best Answer

Let's take it term by term

4x* 2x^2  =  4*2*x*x^2  =  8x^3

4x *(-7x) =  4*(-7)*x*x = -28x^2

4x*3 = 4*3*x = 12x

Put it all together...

8x^3 - 28X^2 + 12x

And that's it ... !!!

 

CPhill Jun 17, 2014

39 Online Users

avatar
avatar